Bio‐Derived Fluorescent Carbon Dots for Metal Sensing and DNA Binding Applications. Issue 1 (2nd January 2023) - Daphne Jacinth Gracia, K.; Sheeba Thavamani, S.; Peter Amaladhas, T.
Abstract: Tunable optical and electronic properties of the fluorescent carbon dots have drawn significant research interests over the years mainly owing to their sensing and photocatalytic applications. In this work, highly fluorescent nitrogen doped carbon dots [N−CDs] have been synthesised from Quercus infectoria via hydrothermal treatment. The structural, optical properties and the surface functionalities of the synthesised N−CDs are analysed with the help of various analytical techniques. The spherical shaped N−CDs exhibit an average particle size of 5 nm. Dual turn‐on‐off fluorescent sensors have been developed to sense Fe(III) and cysteine with detection limit of 1.88×10 −8 M and 7.8×10 −5 M respectively. The synthesised N−CDs exhibited excellent sensitivity in the in vitro detection of Fe(III) in ferric citrate supplements with a detection limit of 1.43×10 −7 M. Interaction between ct‐DNA and N−CDs with a binding constant of 1.32 (mg/mL) −1 indicates its potency in designing drugs. The fluorescent nature of the N−CDs envisions its application to image SKMEL cells and L6 cells. This work may be extended for the use of N−CDs for diverse applications including in vivo sensing. Abstract : Nitrogen doped carbon dots synthesized from Quercus infectoria have an enhanced quantum yield of 39.96 %. They serve as efficient turn off sensor towards ferric ions and turn on sensor towards cysteine. Their excellent interaction with DNA, utility to image L6 cells and SKMEL cells and as patterning agents is reported.